1998
DOI: 10.1111/j.1530-0277.1998.tb03871.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Action of Acamprosate. Part I. Characterization of Spermidine‐Sensitive Acamprosate Binding Site in Rat Brain

Abstract: It has been suggested that the anticraving drug, acamprosate, acts via the glutamatergic system, but the exact mechanism of action is still unknown. The aim of this study was to characterize [3H]acamprosate binding and establish whether this showed any relation to sites on the NMDA receptor complex. We found saturable specific binding of [3H]acamprosate to rat brain membranes with a KD of 120 microM and a Bmax of 450 pmol/mg of protein. This acamprosate binding site was sensitive to inhibition by spermidine (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(48 citation statements)
references
References 18 publications
2
46
0
Order By: Relevance
“…Acamprosate has been considered as a partial co-agonist of the NMDA receptor. 6,7 These actions of acamprosate are compatible with the hypothesis that this medication suppresses the hyperactivity associated to high levels of excitation of the glutamate receptor during alcohol withdrawal in dependent patients. Therefore, this medication reduces the toxicity induced by glutamate.…”
Section: Introductionsupporting
confidence: 70%
“…Acamprosate has been considered as a partial co-agonist of the NMDA receptor. 6,7 These actions of acamprosate are compatible with the hypothesis that this medication suppresses the hyperactivity associated to high levels of excitation of the glutamate receptor during alcohol withdrawal in dependent patients. Therefore, this medication reduces the toxicity induced by glutamate.…”
Section: Introductionsupporting
confidence: 70%
“…Acamprosate also has some effects in preventing aversive effects associated with ethanol withdrawal (Spanagel et al, 1996b;Cole et al, 2000). In vitro studies have suggested that acamprosate may be acting as a partial co-agonist at the N-methyl-D-aspartate receptor Zeise et al, 1993;Dahchour et al, 1998;Koob et al, 2002;al Qatari et al, 1998;Naassila et al, 1998), a neuropharmacological action that might explain its blockade of excessive drinking and attenuation of the motivational effects of abstinence from ethanol. The present study was initiated to test the hypothesis that the anti-alcohol-dependence effects of acamprosate might generalize to opiate dependence.…”
Section: Discussionmentioning
confidence: 99%
“…NMDA receptors are involved with long-term potentiation, an electrophysiological phenomena involving longlasting, activity-dependent increases in the strength of synaptic transmission, which appears to be an intermediate step required for memory storage (Malenka 1991). Recent evidence suggests that acamprosate may act as a partial co-agonist at the NMDA receptor (Naassila et al 1998;al Qatari et al 1998). The acamprosate cognitive data are consistent with pre-clinical and human studies that show d-cycloserine, a partial agonist of the glycine site on the NMDA receptor, did not affect acquisition of new learning, but did improve performance during the retention phase of tasks Pussinen et al 1997;Tsai et al 1999;Wesnes et al 1991).…”
Section: Bj Mason Et Almentioning
confidence: 99%